Graceland. The complete first season [videorecording (DVD)] - Eastin, Jeff; Ehrlich, Jon (2014)
It seems like a sweet deal when new FBI agent Mike Warren's first assignment lands him in a beautiful L.A. beachfront mansion with other young undercover government agents, including his idol, legendary FBI agent Paul Briggs. But loyalties are tested and lives are put on the line when Warren is ordered to secretly investigate Briggs.